A Functional Subnetwork Approach to Designing Synthetic Nervous Systems That Control Legged Robot Locomotion - Szczecinski, Nicholas S.; Hunt, Alexander J.; Quinn, Roger D. (Frontiers in Neurorobotics, 2017)
A dynamical model of an animal’s nervous system, or synthetic nervous system (SNS), is a potentially transformational control method. Due to increasingly detailed data on the connectivity and dynamics of both mammalian and insect nervous systems, controlling a legged robot with an SNS is largely a problem of parameter tuning. Our approach to this problem is to design functional subnetworks that perform specific operations, and then assemble them into larger models of the nervous system. In this paper, we present networks that perform addition, subtraction, multiplication, division, differentiation, and integration of incoming signals. Parameters are set within each subnetwork to produce the desired output by utilizing the operating range of neural activity, $R$, the gain of the operation, $k$, and bounds based on biological values. The assembly of large networks from functional subnetworks underpins our recent results with MantisBot.